As artes de fazer cotidianas de trabalhadoras domésticas inseridas em micro dimensões organizativas da vida social - Juliana Cristina Teixeira; Caroline Rodrigues Silva (Ciências Sociais Unisinos)
The main objective of this paper is to know the daily practices (strategies and tactics) of housemaids who represent their arts of making. The expression arts of making is present in Certeau (1998), an author who theoretically brings us the possibility of presenting a paper dedicated to ordinary women. The research is qualitative and involved a corpus with the production of speeches obtained through interviews with housemaids. These interviews were open and also semi-structured, seeking to apprehend their arts. The theoretical-methodological approach used refers to ACD (Critical Discourse Analysis). This paper allowed the approach of different daily and ordinary knowledge that circulate among the practices of domestic servants within what was called a more excellent knowledge: the knowledge to manage and participate in the management of organized social life. Introducing the perspective of the organized social life of domestic workers, we refer to the study of organized social life, identifying the subjects studied as authors of micro-practices that directly contribute to critical organizational policies, sometimes ignored, in society and mainstream studies.